Carbazole scaffolds in cancer therapy: a review from 2012 to 2018 - Samar Issa; Anthony Prandina; Nicolas Bedel; Pål Rongved; Saïd Yous; Marc Le Borgne; Zouhair Bouaziz (Taylor & Francis Group, 2019)
For over half a century, the carbazole skeleton has been the key structural motif of many biologically active compounds including natural and synthetic products. Carbazoles have taken an important part in all the existing anti-cancer drugs because of their discovery from a large variety of organisms, including bacteria, fungi, plants, and animals. In this article, we specifically explored the literature from 2012 to 2018 on the anti-tumour activities reported to carbazole derivatives and we have critically collected the most significant data. The most described carbazole anti-tumour agents were classified according to their structure, starting from the tricyclic-carbazole motif to fused tetra-, penta-, hexa- and heptacyclic carbazoles. To date, three derivatives are available on the market and approved in cancer therapy.